Energy savings potential of the high-rise office building stock. A case study of Belo Horizonte, Brazil: a case study of Belo Horizonte; Brazil - Tatiana Paula Alves (2017)
This study develops a framework to identify and analyse the energy savings potential of an existing building stock category. The methodology consists of six basic steps: (1) a method for obtaining reference buildings, (2) dynamic archetype model simulations, (3) an energy consumption baseline estimation, (4) energy retrofit measures selection and a cost optimal pathway analysis, (5) developing energy saving scenarios and (6) estimating building stock energy savings potential. In order to apply the proposed methodology, a case study took place in the city of Belo Horizonte, Minas Gerais, Brazil. Firstly, the city plan, the land use regulations and the building construction codes of Belo Horizonte were investigated in a temporal and spatial perspective. Secondly, a local city council database based on land tax information was used to study basic high-rise office building features. Thirdly, a field study was conducted based on the proposed building typology classification. The information gathered from the three inputs was used to obtain three reference buildings and describe their prevalent attributes. For each reference building, building archetype energy models were created and simulations were performed in EnergyPlus to assess their Energy Use Intensity (EUI). The BaseCase baseline of energy consumption was then estimated based on the simulated EUI of each archetype energy model. The results of the BaseCase baseline analysis emphasized the role of technical choices in reducing electric energy consumption, particularly the ones related to the HVAC system. They also showed that there are growing evidences that the high-rise office buildings are becoming more energetically intense. Furthermore, in order to assess the building stock energy savings potential, retrofit measures were selected based on their technical feasibility and suitability. A local sensitivity analysis was then used to prioritize the building retrofit measures and a sequential search optimization technique was applied in order to identify the cost optimal pathway for implementing the measures. Finally, three scenarios were developed based on the cost optimal pathway analysis results. The scenario projections were then estimated and compared to the BaseCase projection in order to assess the energy savings potential of the office building stock. The saving scenario results highlighted that there are significant opportunities for energy efficiency improvements in the existing high-rise office building stock of the city. Using current technologies, cost effective energy savings of up to 24% would be possible in the high-rise office building stock by 2036.Regardless costs, by the year 2036, deeper retrofit packages could unlock savings up to 28%. Overall, the disaggregated scenario projections emphasized the significance of dealing with the existing high-rise office building stock but also highlighted that to shorten the current building stock consumption over the next 20 years the policy makers will have to pay close attention to the upcoming buildings.